BLOCKCHAIN AND INTELLECTUAL PROPERTY RIGHTS: IMPLICATIONS FOR CREATIVEPRENEURS - Wijaya Wijaya; Maria Clara Reyes; Samantha Gonzales (Yayasan Adra Karima Hubbi, 2025)
The rapid growth of blockchain technology has raised significant interest across various sectors, including intellectual property (IP) management. In the creative industries, where intellectual property rights (IPRs) are pivotal, blockchain offers a promising solution for ensuring the protection, tracking, and transfer of creative works. With the increasing prevalence of digital content, creativepreneurs face complex challenges related to the ownership and distribution of their creations. Blockchain’s decentralized, transparent, and immutable features make it a potential game-changer in addressing these challenges. This research aims to examine the implications of blockchain technology on intellectual property rights for creativepreneurs. It explores how blockchain can facilitate better protection, enforcement, and monetization of IP assets in the creative industries. A qualitative research approach is employed, utilizing case studies of creativepreneurs who have implemented blockchain solutions in their IP management practices. Interviews with industry experts and stakeholders are also conducted to gather insights into the practical application and effectiveness of blockchain for IP protection. The study reveals that blockchain can enhance IP protection by providing verifiable records of ownership and transactions, reducing the risk of counterfeiting and infringement. Creativepreneurs also report improved trust and efficiency in licensing agreements, ensuring fair compensation for their work.